Challenge Indonesia's Regulation of International Crime in Illegal Logging - Yuniar Ariefianto (Faculty of Law, Universitas Sebelas Maret, 2021)
Wild Logging is difficult to eradicate because it is not only a matter of how the law must be enforced but also because it involves many issues, such as the participation of law enforcement officers. The study employs the descriptive-analytic approach to acquire in-depth data that will be meaningful. Examine the challenges of transnational crime related to illegal logging. The conclusion, Illegal Logging falls under the category of Transnational Crime because its activities frequently involve more than one nation, both in terms of preparation, planning, and supervision, as well as in terms of the damage it causes.